Isa‒NHC‒catalyzed intermolecular Stetter reaction of aromatic aldehydes with maleimides: An efficient access to 3‒aroylsuccinimides. Issue 16 (19th April 2018) - Ahire, Milind M.; Mhaske, Santosh B.
Abstract: An intermolecular Stetter reaction of aromatic aldehydes with maleimides has been developed using thiazolylidene salt derived Isa‒NHC as an efficient organocatalyst. The synthesized Stetter products "3‒aroylsuccinimides" are important building blocks for the synthesis of natural products and bioactive compounds. The reaction conditions are mild, and various substituents on aromatic aldehyde and maleimide nitrogen were tolerated. Graphical abstract: Image 1